Biochemical Parameters of Thyroid Profile in Relation to Pregnancy in Last Trimester - Samia Sarwar, Iram Qamar, Tehreem Mehmood, Junaid Iqbal, Shahid Nazeer, Gul-E-Rana, Rizwan Saeed, Syed Husnain Bashir Bukhari, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Thyroid hormones are basic for foetal development during pre and after birth period. During pregnancy, expanded amalgamation of thyroid hormones is required to meet fetal requirements, which leads to tall necessity of iodine. Pregnancy could be a stress for thyroid organ; it influences 3% women amid pregnancy and 10% ladies of child bearing age. About 18-20% of Australian ladies have thyroid counter acting agent positive test during first trimester of pregnancy. Objective: To study the relationship of thyroid profile parameters in relation to Pregnant females in last trimester of pregnancy Material and Methods Study design: Cross sectional Settings: Holy Family Hospital Rawalpindi Duration: 6 months, 1st July 2021 to 31st December 2021 Data Collection Procedure: A cross sectional study was conducted on 50 patients. The study was conducted in Holy Family Hospital Rawalpindi. Ethical approval was taken from ethical committee. An educated consent was taken from the participants. Study members were pregnant mothers with pregnancy going to antenatal clinic during last trimester of pregnancy. All subjects were examined for any indications and signs of hypothyroidism and hyperthyroidism. This was cross-sectional study Simple convenient sampling technique was applied and sample was calculated using classical test estimate calculation equation of Cochran. Thyroid profile parameters were assessed by ELIZA strategy. Results: A group of fifty healthy pregnant females was selected. The mean age of pregnant females of maternal group was 28.5+6.5. Mode of delivery in females as 28(56%) normal spontaneous vaginal delivery and 22(44%) undergoes C-section. Standard error of mean, Standard deviation and percentile values were calculated in maternal group of females. Conclusion: Trimester particular reference ranges of TSH, FT4 and FT3 of our study were lower than international recommenced levels of 2017 Guidelines of American Thyroid Affiliation. These values may be utilized to compare thyroid disease in pregnancy in our area